Electronically optimized diazirine-based polymer crosslinkers. Issue 25 (14th June 2022) - Musolino, Stefania F.; Mahbod, Mahshid; Nazir, Rashid; Bi, Liting; Graham, Hamish A.; Milani, Abbas S.; Wulff, Jeremy E.
Abstract : Electronically optimized bis-diazirine crosslinkers allow aliphatic polymers to be crosslinked with up to 10-fold improved efficacy, relative to earlier designs. Activation is achieved using modest temperatures or through UV or visible light. Abstract : Topical application of diazirine-based crosslinkers can upgrade the mechanical properties of low-functionality commodity plastics by engaging in rapid C–H insertions along the polymer chain. Here we describe an effective strategy to improve the performance of diazirine reagents through electronic optimization of the trifluoromethyl aryl diazirine warhead. A prototypically optimized bis-diazirine is shown to be >10-fold more effective than earlier best-in-class crosslinkers. The superior performance—attributed to better stabilization of intermediate singlet carbenes—confers increased tear resistance and enhanced tensile strength to ultra-high molecular weight polyethylene fabric, at lower loadings than was previously achievable for any crosslinking reagent. Electronically optimized diazirines can also be activated at lower temperatures and longer wavelengths than traditionally employed analogues, for the first time enabling fast, high-yield crosslinking of unfunctionalized aliphatic substrates using visible light. These advances pave the way for far-ranging improvements to the design of new diazirine-containing crosslinkers, biological probes, adhesives, and related reagents.